2011
DOI: 10.1021/ac202243r
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Mass Tag Protein Labeling for Top-Down Identification and Quantification

Abstract: Top-down mass spectrometry holds tremendous potential for characterization and quantification of intact proteins. So far, however, very few studies have combined top-down proteomics with protein quantification. In view of the success of isobaric mass tags in quantitative bottom-up proteomics, we applied the tandem mass tag (TMT) technology to label intact proteins and examined the feasibility to directly quantify TMT-labeled proteins. A top-down platform encompassing separation via ion-pair reversed-phase liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 54 publications
(79 reference statements)
0
57
0
Order By: Relevance
“…To address this limitation, the same group followed up with a model to account for the number of amino acids to be labeled in a given proteoform and the incorporation efficiency of the amino acid, and successfully deployed top-down SILAC in human embryonic stem cells (92). Additionally, a pilot study applying the tandem mass tag (TMT) quantification strategy often used in BUP (93) has demonstrated the feasibility of TMT-based quantitation in TDP (94). This method is appealing because this in vitro labeling technique is dependent on tandem MS, so that labeled pairs will have the same chromatographic profiles.…”
Section: Coverage and Quantitation Of Intact Proteomesmentioning
confidence: 99%
“…To address this limitation, the same group followed up with a model to account for the number of amino acids to be labeled in a given proteoform and the incorporation efficiency of the amino acid, and successfully deployed top-down SILAC in human embryonic stem cells (92). Additionally, a pilot study applying the tandem mass tag (TMT) quantification strategy often used in BUP (93) has demonstrated the feasibility of TMT-based quantitation in TDP (94). This method is appealing because this in vitro labeling technique is dependent on tandem MS, so that labeled pairs will have the same chromatographic profiles.…”
Section: Coverage and Quantitation Of Intact Proteomesmentioning
confidence: 99%
“…Proteins from our five treatments plus a t ϭ 0 sample representing the unstressed proteome were labeled using a TMT sixplex tagging kit (Thermo Scientific, East Riding, UK) comprising an isobaric set of six mass tags with five isotopic substitutions. Each tag produces a unique reporter ion during MS/MS fragmentation analysis enabling concurrent identification and quantification of proteins in different samples by labeling of digested proteins at the peptide level (bottom-up strategy) (68) or by labeling at the protein level followed by to tryptic digestion (top-down strategy) (69). Simultaneous processing of six samples minimizes analytical variation introduced by differences in gel loading or extraction and eliminates the need for six individual analyses that would be affected by LC-MS/MS signal fluctuations between operations.…”
mentioning
confidence: 99%
“…Several researchers have successfully applied various labeling techniques, like those often seen in quantitative bottom-up workflows, to intact protein analysis, including a study by our own group that quantified over 200 intact protein pairs by 14 N/ 15 N labeling in an anoxic yeast model [9]. In addition, studies have applied in vitro differential cysteine labeling [10] and tandem mass tag (TMT) workflows to perform MS1 and MS2-based quantitation of intact proteins [11]. However, these in vitro labeling methods are limited in their application to large-scale top-down quantitation studies, as differential labeling was found to alter chromatographic retention time and the existence of multiple precursor charge states in top-down measurements greatly complicates isobaric labeling experiments.…”
Section: Introductionmentioning
confidence: 99%